Análise do processo de difusão da inovação dos produtos de moda segundo a teoria de Rogers - Campelo, Alessandra Helena Gomes (2018)
Fashion designers and the entire production chain are governed by the laws of demand and supply. The study of the diffusion of innovations proposed by Rogers aims to explain how the process of adopting innovation within a given social system takes place. The diffusion curve aims to map the five types of consumers of innovative products in order to map the behavior predicted by the Rogers Theory categories. If proven, the analysis of the process and the diffusion of innovations can be a useful tool for the segmentation surveys of the fashion market.